2008
DOI: 10.1007/s11199-008-9521-4
|View full text |Cite
|
Sign up to set email alerts
|

Objectified Body Consciousness in a Developing Country: A Comparison of Mothers and Daughters in the US and Nepal

Abstract: Self-objectification (Fredrickson and Roberts 1997) has been related to negative psychological consequences in U.S. women. However, little cross-cultural research has been done. We compared convenience samples of American and Nepali women on two measures of selfobjectification. Pairs of Nepali mothers and daughters (N=23) and pairs of U.S. mothers and daughters (N=24) completed a quantitative and a qualitative measure of selfobjectification. Cultural and generational differences were found. Nepali women enga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
26
2
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 31 publications
5
26
2
1
Order By: Relevance
“…This modest relationship is possibly due to the significant age difference between mothers and daughters, and therefore the difference in the gender socialization and expectations experienced by mothers and daughters -which is similar to past findings (Crawford et al 2009;McKinley 1999). For instance, older women in Australia report being more satisfied with their bodies than younger women (e.g., Tiggemann and McCourt 2013), and self-objectification, habitual body monitoring, and body surveillance was also found to decrease with age in samples of U.S. women (McKinley 1999).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…This modest relationship is possibly due to the significant age difference between mothers and daughters, and therefore the difference in the gender socialization and expectations experienced by mothers and daughters -which is similar to past findings (Crawford et al 2009;McKinley 1999). For instance, older women in Australia report being more satisfied with their bodies than younger women (e.g., Tiggemann and McCourt 2013), and self-objectification, habitual body monitoring, and body surveillance was also found to decrease with age in samples of U.S. women (McKinley 1999).…”
Section: Discussionsupporting
confidence: 87%
“…Past research has found inconsistent results pertaining to mothers' and daughters' self-objectification (i.e., Crawford et al 2009;Katz-Wise et al 2012;McKinley 1999), but we found a positive direct effect of mothers' self-objectification on their daughters' self-objectification. This is consistent with social learning theory's premise that daughters may learn to self-evaluate by observing behaviors related to their mothers' self-evaluation.…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…Moreover, social and psychological experiences of pregnancy, and cultural values and ideals associated with pregnant and postpartum women, vary across cultures and contexts (e.g., Becker 1998). Of note, however, a recent study by Crawford et al (2009) exploring objectified body consciousness among young adult women and their mothers in the US and Nepal highlights the importance of body functionality among young Nepali women. Thus, body functionality may be an important, and inclusive, aspect of body image to consider in future studies of objectification theory among women in the developed and developing world.…”
Section: Discussionmentioning
confidence: 99%
“…Future research should investigate whether self-objectification also encompasses the treatment of oneself as a tool for a specific end (instrumentality), as lacking in autonomy and self-determination (denial of autonomy), as lacking in agency and activity (inertness), as interchangeable with others of the same or different types (fungibility), as permissible to break, smash, or break into (violability), as something that is owned by another (ownership), and/or as something whose experience and feelings do not need to be considered (denial of subjectivity). All or some aspects of this broader phenomenological experience of self-objectification may be relevant to womenÕs motivation to support the status quo and should be further investigated, especially across other cultures and subcultures where the objectification of women is pervasive and womenÕs agency is directly thwarted (Crawford et al, 2009;Jeffreys, 2005;Moradi, 2010Moradi, , 2011Tiggemann, Verri, & Scaravaggi, 2005;United Nations, 1995).…”
Section: Some Next Stepsmentioning
confidence: 99%